Absortive capacity as the key to successful innovation and technology leadership in improving business performance at double u steak by chef widhi bekasi in bekasi city - Subagdja, Faizh Hafidz; Ghifari, Muhamad Naufal (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study investigates the influence of Marketing Innovation, Global Expansion, and Prowgrowth Absorptive Capacity on Technology Leadership and Business Performance among small and medium-sized enterprises (SMEs) in the food and beverage sector. Guided by the Dynamic Capabilities Theory and Absorptive Capacity Theory, the research explores how knowledge absorption and technological leadership contribute to sustainable competitive advantage. Data were collected from [insert sample size] respondents and analyzed using Structural Equation Modeling (SEM) with AMOS version 26. The model achieved a good fit (χ² = 118.673; p = 0.076; RMSEA = 0.022; CFI = 0.993), confirming the reliability and validity of the constructs. Results indicate that Marketing Innovation significantly enhances both Absorptive Capacity and Technology Leadership, while Global Expansion shows no significant effect. Absorptive Capacity and Technology Leadership each have positive impacts on Business Performance, with Technology Leadership partially mediating their relationship. The study concludes that innovation and knowledge integration are stronger drivers of performance than market expansion, emphasizing the need for SMEs to strengthen learning-based innovation and digital leadership strategies.